2020
DOI: 10.1159/000507088
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Heads-Up versus Binocular Microscope Visualization Systems in Anterior and Posterior Segment Surgeries: A Retrospective Study

Abstract: Background: Three-dimensional (3D) visualization systems, also known as heads-up systems, are now available for eye surgery and as with every new device there is need for a specific evaluation. Objectives: The aim of this study was to compare the efficiency, surgical comfort, and safety of a 3D visualization system to a standard binocular microscope (BM) in routine ophthalmologic procedures. Method: After a 4-week training period, a 3D visualization system (Ngenuity, Alcon ®) available in one of the Robert Deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 10 publications
(27 reference statements)
2
47
0
Order By: Relevance
“…In our study, mean surgical duration with 3D DAVS was comparable to CAM. This result is supported by works of Coppola et al in 2017, Romano et al in 2018, Kumar et al in 2018, Palacois et al in 2019, Babu et al in 2020 and Berquet et al [ 4 10 11 13 17 22 ] Few studies have reported longer surgical duration but this can be attributed to learning curve of the surgeon. [ 12 ]…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In our study, mean surgical duration with 3D DAVS was comparable to CAM. This result is supported by works of Coppola et al in 2017, Romano et al in 2018, Kumar et al in 2018, Palacois et al in 2019, Babu et al in 2020 and Berquet et al [ 4 10 11 13 17 22 ] Few studies have reported longer surgical duration but this can be attributed to learning curve of the surgeon. [ 12 ]…”
Section: Discussionsupporting
confidence: 57%
“…[ 25 ] Similar results leading to the superior surgeon's ergonomics have also been reported by many other workers. [ 4 5 8 9 10 11 12 19 20 21 22 25 18 ] 3D DAVS has also been described to perform surgery in patients with disabling musculoskeletal deformities (e.g., Kyphosis) when operating on a CAM is quite challenging. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] Moreover, 3D imaging allows observers to see exactly what the surgeon sees during the surgery, improving effectiveness in teaching and learning. 4,6,7 Since first developed in 2009, 8 heads-up surgery has gained increasing popularity in ophthalmic surgery, including Descemet membrane endothelial keratoplasty (DMEK), 9,10 cataract surgery, [11][12][13][14] and vitreoretinal surgery. 4,[15][16][17][18][19] Current reports on heads-up surgery mainly focus on its use in vitreoretinal disease because of its advantage of a lower endoillumination level and higher depth of field.…”
Section: Introductionmentioning
confidence: 99%
“…This difference in the preference may be due to the image latency period that had a more de nite effect in the anterior procedures. This preference between the steps might change over the learning curve and many studies emphasize that surgeons felt more comfortable with Ngenuity in both anterior and posterior procedures after 3 or 4 surgeries which was considered to a short period [7,8].…”
Section: Some Studies Have Reported Discomforts Such As Headache Nausmentioning
confidence: 99%